A Rare Case of Penile Metastases as a Harbinger of Primary Pulmonary Adenosquamous Carcinoma - Partha Hota; Tejas N. Patel; Xiaofeng Zhao; Carrie Schneider; Omar Agosto (Case Reports in Radiology)
Although lung cancer has a high propensity for distant metastatic disease, penile metastases from primary lung neoplasms are considered particularly rare. A 71-year-old male presented to our hospital with a rapidly enlarging hard palpable penile mass. MR imaging demonstrated two penile masses centered in the left and right corpus cavernosa. Subsequent CT imaging revealed a spiculated pulmonary mass in the right upper lobe with PET/CT, MRI, and surgical exploration, demonstrating evidence of metastases to the left adrenal gland, right subscapularis muscle, brain, and small bowel. Tissue sampling of lesions in the small bowel, right subscapularis muscle, and penis demonstrated histopathology consistent with an adenosquamous carcinoma which in combination with the appearance of the right upper lobe mass on PET/CT imaging suggested the patient’s lung cancer as the primary lesion. Prior to our case, pulmonary adenosquamous carcinoma metastasizing to the penis has only been reported once in the literature. Herein, we report a rare case of penile metastases as the presenting sign of metastatic pulmonary adenosquamous carcinoma characterized with PET/CT and MR imaging.